The identification of opportunities for innovations through collecting problems from citizens - Karine Oganisjana; Konstantins Kozlovskis (Journal of Open Innovation: Technology, Market, and Complexity, 2019)
Customer engagement in different phases of creation of new products and services is argued to be a significant success factor by some scholars and practitioners, and unnecessary-by others. The paper analyses the findings of a pilot study, conducted with the intention to see whether ordinary citizens from different countries could highlight problems which really could bring forth ideas for innovative products or services. The data were collected via electronic survey with the further qualitative content analyses of the problems that, to the respondents' minds, are worth solving. The expert group analysis of the ideas which derived from the problems was conducted to decide the feasibility of the approach, whose efficiency was concluded not to be high. Reliability and consistency of the experts' assessments were tested using statistical software SPSS 20 based on the correlation analysis of five criteria-usefulness, social impact, customer base, frequency of use, and novelty. The research revealed 16 groups of problems.
Keywords: 650; bank of problems; citizen engagement; innovation opportunities; problem derived innovation